Pengembangan Desain Model Desain Kemp Dalam Pembelajaran - Reksiana Reksiana (Alim | Journal of Islamic Education, 2022)
The purpose of this study is to find out how the development of Kemp's learning design model in learning. The method used in this research is Library Research. The primary data sources in this study are: the main books related to the development of the Kemp Model such as: Kemp, J. E., Morrison, G. R., & Ross, S. V Design effective instruction, Serhat Kurt, “Kemp Design Model, Ratumanan dan Imas Rosmiati, Perencanaan Pembelajaran, and others. Meanwhile, the secondary data in this study are: international journals and national journals related to the development of the Kemp learning model. The steps in this study: first, obtain data. Second, look for information that supports the topic. Third, reinforce the focus of the study from the reading material. Fourth, reviewing and enriching reading materials and classifying them. Fifth, conduct an analysis and draw conclusions. The findings of this study are: Kemp's learning design model can be used flexibly and can be started simultaneously from the nine stages. The development of this Kemp model of learning can be implemented at every level such as elementary, secondary, and tertiary levels. This model can also be combined using descriptive research designs and quasi-experiments for field testing. In addition, this Kemp model is also effectively used by teachers and students in developing teaching materials for a subject or course